A meta-evolutionary selection of constituents in ensemble differential evolution algorithm - M.T., Indu; C., Shunmuga Velayutham (Expert systems with applications, 2022)
A Meta-evolutionary Selection of Constituents in Ensemble DE (MeSCEDE) framework is proposed in this paper to automate the design of high-level multi-population ensemble Differential Evolution (DE) algorithms. The automated design of high-level multi-population ensemble DE algorithms involves both automated selection of constituent DE algorithms for the ensemble and automated configuration of ensemble related parameters. Grammatical Evolution has been used as the meta-evolutionary algorithm in MeSCEDE to search the space of design choices so as to evolve effective ensemble design(s) for given problem(s). The simulation experiments carried out in this paper involve applying MeSCEDE to evolve ensemble DE designs for solving 30-dimensional CEC’17 benchmark functions. The effectiveness of the evolved designs are validated on 30 and 50-dimensional CEC’14 functions as well as on 22 real-world problem instances from CEC’11 benchmark suite. The MeSCEDE evolved designs have exhibited a competitive performance against state-of-the-art ensemble DE algorithms. In addition, the potential of MeSCEDE has been demonstrated against irace, a state-of-the-art algorithm configurator. All simulation experiments reiterate the potential of MeSCEDE towards evolving effective and robust ensemble DE designs. •Automated design of ensemble differential evolution (DE) algorithm is presented.•The proposed approach is Meta-evolutionary Selection of Constituents in Ensemble DE.•The approach uses grammatical evolution as the meta evolutionary algorithm.•The approach is demonstrated on CEC’17, CEC’14 and CEC’11 benchmark suites.•Relieves the practitioners from the difficult task of algorithm configuration.